Repeatability, reproducibility, and agreement of three methods for finding the mechanical axis of the human tibia. Issue 11 (15th August 2022) - Simileysky, Alexander; Hull, Maury L.
Abstract: Background: Identifying the center of the talocrural joint is crucial in defining the tibia's mechanical axis, which is used in a variety of applications such as a reference for measuring alignment variables following total knee arthroplasty. The objectives of this study were to 1) describe a new method for determining the center of the talocrural joint, 2) determine the repeatability and reproducibility of the new method and two previously described methods for locating the center, 3) determine the limits of agreement between pairs of methods, and 4) determine angular differences in the coronal and sagittal planes between tibial mechanical axes generated by the different methods. Methods: The new area centroid method identified the center of the talocrural joint as the centroid of the distal tibia's articular surface. Previously described methods included the diagonal intersection and biplanar methods. For each method, the medial-lateral, anterior-posterior, and proximal-distal coordinates of the talocrural joint center and angular differences between tibial mechanical axes were determined in thirteen 3D full tibia bone models. Results: For the area centroid method, ICC values indicated excellent repeatability (0.97) and reproducibility (0.92). For the biplanar method, ICC values indicated good repeatability (0.86) and fair reproducibility (0.40). For the diagonal intersection method, ICC values indicated moderate repeatability (0.71) and fair reproducibility (0.46). Limits of agreement were tightest between the area centroid and diagonal intersection methods (± 4.1 mm). Angular differences between tibial mechanical axes were limited to 3°. Conclusion: The area centroid method locates the anatomic center of the talocrural joint, offers better repeatability and reproducibility than existing methods, and is recommended when identifying the tibial mechanical axis.